Identification of bioactive metabolites and evaluation of in vitro anti-inflammatory and in vivo antinociceptive and antiarthritic activities of endophyte fungi isolated from Elaeocarpus floribundus blume. (12th June 2021) - Mazumder, Kishor; Ruma, Yasmeen Nazim; Akter, Rasheda; Aktar, Asma; Hossain, Mir Monir; Shahina, Zinnat; Mazumdar, Santosh; Kerr, Philip G.
Abstract: Ethnopharmacological relevance: Functional disability associated with rheumatoid arthritis (RA), a chronic inflammatory autoimmune disease is a challenging concern in healthcare systems. Along with environmental factors and epigenetic disorders, multiple pathways are reported as prominent mechanism for the progression of RA symptoms including; pain, swelling and stiffness of joints. Elaeocarpus floribundus Blume has been used as a folklore medicine for RA from ancient times. This plant harbours a suite of endophytic fungi that produce a range of metabolites of potential interest. Thus, for the establishment of a scientific basis for this folklore use, it is essential to find out the involvement, if any, of the endophytic fungi living in this plant and the metabolites they elaborate, for the management of RA. Aim of the study: This study was designed to isolate, identify and evaluate the in vitro anti-inflammatory and in vivo antinociceptive and antiarthritic activities of the compounds produced by the endophytic fungi living in different parts of Elaeocarpus floribundus Blume. Materials and methods: Endophytic fungi from different parts of the plant were isolated and cultured for the production of secondary metabolites. Chromatographically fractionated fungal extracts were assessed for anti-inflammatory and antinociceptive activities. For the evaluation of anti-inflammatory activity, in vitro cyclooxygenase (COX1/COX2) and 5-lipoxygenase (5-LOX) inhibitory assays were performed. For the evaluation of in vivo antinociceptive activity, hot plate acetic acid induced writhing, and formalin induced paw licking methods were adopted, whereas complete Freund's adjuvant (CFA) induced poly-arthritic method was adopted for the evaluation of antiarthritic activity. The most effective fraction was analyzed by liquid chromatography-mass spectroscopy (LC-MS) in search of the bioactive extracellular metabolites. Results: Five endophytic fungi viz. Aspergillus fumigatus, Aspergillus niger, Rhizoctonia oryzae, Rhizopus oryzae, and Syncephalastrum racemosum were isolated. COX1/COX2 and 5-LOX inhibitory assays state that the Aspergillus niger fraction possesses the greatest activity against these enzymes of inflammatory process. In vivo antinociceptive showed significant (***P<0.001) reduction of pain in a dose dependent manner. As well, significant (***P<0.001) reduction of paw volume was observed in CFA induce poly-arthritic test. LC/MS analysis of the Aspergillus niger fraction revealed the presence of bioactive compounds including tensyuic acid, hexylitaconic acid, chlorogenic acid, nigragillin, TMC-256C1, asnipyrone B, asperenone, fumaric acid and fusarubin, all having reported pharmacological activities. Conclusion: The present study demonstrates that secondary metabolites produced by endophytic fungi living in various parts of Elaeocarpus floribundus Blume had potential to relief pain and inflammation. The endophytes were found to contain multiple biomolecules effective in rheumatoid arthritis. These findings provide a rationale for the folklore use of the plant in the management of rheumatoid arthritis. Graphical abstract: Image 1